Sexual and reproductive health "Train The Trainer" programs in low- and middle-income countries: a scoping review - Felicity R A Hughes; Jessica R Botfield; Kevin McGeechan (Journal of Global Health Reports)
# Background Universal access to reproductive health care including family planning and sexual health care are recognised as human rights and are a key contributor to the United Nations’ (UN) Sustainable Development Goals, yet many people across the globe have limited access to information and services to protect their sexual and reproductive health (SRH). Universal access cannot be achieved without a skilled health workforce. ‘Train the Trainer’ (TTT) approaches are commonly advocated as cost-effective and sustainable options for building health capacity through up-skilling health workforces.